High-entropy ceramic material as well as preparation method and application thereof
By using high-entropy ceramics (HF (1-X)/4ZR (1-X)/4CE (1-X)/4PR (1-X)/4yx) O2-Δ, the existing heat-barrier coating material is solved The problem of insufficient resistance in CMAS corrosion realizes the excellent corrosion resistance of CMAS at high temperature at high temperature.
Patent Information
- Application Number
- CN202411900625.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Existing thermal barrier coating materials show insufficient resistance when facing CMAS corrosion, resulting in premature failure of the coating and insufficient temperature bearing capacity.
Using high-entropy ceramic materials (HF (1-X)/4ZR (1-X)/4CE (1-X)/4PR (1-X)/4yx) O2-Δ, through specific preparation methods, including oxide powder, including oxide powder Preparatory treatment, ball grinding, drying, grinding, sieve, suppression and firing, etc., prepare high -entropy ceramics with excellent anti -CMAS corrosion properties.
When high-entropy ceramic materials face CMAS corrosion, they effectively prevent CMAS from further penetrating into the ceramic layer by generating a corrosion reaction layer of long apatite and massive cubic phases, significantly reducing the corrosion depth and improving the coating's resistance to high-temperature corrosion. .
Smart Images

Figure CN119350026A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermal barrier coatings, and in particular relates to a high entropy ceramic material and a preparation method and application thereof. Background Art
[0002] Thermal barrier coatings (TBCs) technology is a key technology to improve the temperature bearing capacity of aircraft engines. However, with the continuous increase in the operating temperature of aircraft engines, molten environment deposits (CMAS) corrosion has gradually become the main form of thermal barrier coating failure. Traditional thermal barrier coating materials, such as yttria-stabilized zirconia (YSZ), have defects such as premature coating failure and insufficient temperature bearing capacity, and can no longer meet the requirements of aircraft engines to resist high-temperature oxidation, thermal shock and external corrosion. Therefore, it is urgent to develop new thermal barrier coating materials with excellent comprehensive properties such as low thermal conductivity, high hardness and high-temperature corrosion resistance. Rare earth fluorite oxide has the characteristics of low thermal conductivity, high hardness, excellent phase stability and high-temperature corrosion resistance, and has shown great potential in the field of thermal barrier coating materials. It can be used to develop more excellent and reliable thermal barrier coating materials, providing strong support for the development of aircraft engines. Summary of the invention
[0003] In view of the above-mentioned prior art, the present invention discloses a high entropy ceramic material and a preparation method and application thereof, so as to solve the technical problem that the thermal barrier coating material in the prior art has weak resistance to CMAS corrosion.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a high entropy ceramic material, whose chemical formula is (Hf (1-x) / 4 Zr (1-x) / 4 Ce (1-x) / 4 Pr (1-x) / 4 Y x ) 2-δ , where the value range of X is 0.08~0.4, and the value range of δ is 0.1~0.4.
[0005] The present invention also discloses a method for preparing the high entropy ceramic material, which comprises the following steps: S1: The pretreated oxide powders are mixed according to the element composition in the chemical formula, and the mixture is mixed with a dispersant and ball-milled to obtain slurry A. The oxide powders include ZrO2 powder, HfO2 powder, CeO2 powder, Pr6O 11 powder and Y2O3 powder; S2: drying, grinding, sieving and pressing the slurry A to obtain a prefabricated embryo body; S3: firing the prefabricated body, then crushing the fired body into powder, mixing the powder and a dispersant and ball milling to obtain slurry B; S4: drying, grinding, sieving, granulating and pressing the slurry B to obtain an embryo body; S5: Firing the embryo to obtain.
[0006] Based on the above technical solution, the present invention can also be improved as follows.
[0007] Furthermore, the pretreatment of the oxide powder in step S1 is: calcining at 800-1000°C for 2-3h; the particle size of the oxide powder is 40-100nm; ZrO2 powder, HfO2 powder, CeO2 powder, Pr6O 11 The purity of powder and Y2O3 powder is ≥99.9%.
[0008] Furthermore, the dispersant is anhydrous ethanol, and the mass ratio of the oxide powder to the anhydrous ethanol in step S1 is 1:0.5-0.6.
[0009] Furthermore, in step S1, the ball milling speed is 300-400 rpm, and the ball milling time is 12-48 h.
[0010] Furthermore, in step S2, the drying temperature is 70-90° C., the drying time is 12-24 h, the grinding time is 5-7 min, the sieving mesh number is 300-500 mesh, and the tablet press is used for pressing, the pressure is 10-20 MPa, and the pressing time is 8-10 min.
[0011] Furthermore, in step S3, the firing temperature is 1200-1400° C., the firing time is 25-50 min; the mass ratio of powder to anhydrous ethanol is 1:0.5-0.6; the ball milling speed is 400-500 rpm, and the ball milling time is 20-50 h.
[0012] Furthermore, in step S4, the drying temperature is 80-100° C., the drying time is 20-40 hours, the grinding time is 5-7 minutes, the sieving mesh number is 500-600 mesh, and the granulation operation is: adding 8% of the total weight of polyvinyl alcohol to the sieved mixed powder and grinding for 5-7 minutes.
[0013] Furthermore, the pressing operation in step S4 is: using a tablet press to press at a pressure of 20-40 MPa for 10-20 min, and then pressing at a pressure of 250-300 MPa for 5-8 min.
[0014] Further, the firing method in step S5 is: heating to 1000°C at a heating rate of 10°C / min, then heating to 1550°C at a heating rate of 5°C / min, keeping the temperature for 20 hours, then heating to 1800°C at a heating rate of 5°C / min, then stopping heating and cooling to room temperature.
[0015] The invention also discloses the application of the high entropy ceramic material in preparing a thermal barrier coating material.
[0016] The beneficial effects of the present invention are as follows: the high entropy ceramic material in the present invention is a new type of rare earth fluorite oxide ceramic material, and its chemical formula is (Hf (1-x) / 4 Zr (1-x) / 4 Ce (1-x) / 4 Pr (1-x) / 4 Y x ) 2-δ , where the value range of X is 0.08~0.4, and the value range of δ is 0.1~0.4. It has excellent anti-CMAS corrosion performance. When the high-entropy ceramic material contacts with molten environment sediments, the rare earth elements contained in the material react with Ca and Si infiltrated in the molten environment sediments to generate long strips of apatite (Ca2RE8(SiO4)6O2). The long strips of apatite and the blocky cubic phase (c-ZrO2) constitute a corrosion reaction layer. The corrosion reaction layer prevents the molten environment sediments from further penetrating into the ceramic layer, thereby reducing the corrosion depth. It can be used to prepare thermal barrier coating materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is the XRD diffraction pattern of the embodiment and the comparative example sample; Figure 2 It is the electron microscope scanning image of the sample of Example 1; Figure 3 It is the electron microscope scanning image of the sample of Example 2; Figure 4 It is the electron microscope scanning image of the sample of Example 3; Figure 5 It is the electron microscope scanning image of the sample of comparative example 1; Figure 6 Element distribution diagram of examples and comparative examples; Figure 7 It is the cross-sectional electron microscope scanning image of the example and comparative example samples after CMAS corrosion for 1 hour; Figure 8 It is the cross-sectional electron microscope scanning image of the example and comparative example samples after CMAS corrosion for 4 hours; Fig. 9 It is the cross-sectional electron microscope scanning image of the example and comparative example samples after CMAS corrosion for 12 hours. DETAILED DESCRIPTION
[0018] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.
[0019] Example 1 A high entropy ceramic material, the chemical formula of which is (Hf 0.23 Zr 0.23 Ce 0.23 Pr 0.23 Y 0.08 ) 1.8 , and its preparation method comprises the following steps: S1: ZrO2 powder, HfO2 powder, CeO2 powder, Pr6O 11 The powder and Y2O3 powder were placed in a zirconia crucible respectively and calcined at 900°C for 2.5h to remove moisture and organic impurities in each oxide powder, so that the purity of each oxide powder was ≥99.9%. Then, the calcined ZrO2 powder, HfO2 powder, CeO2 powder, Pr6O 11 The powder and Y2O3 powder were placed in a zirconia ball mill, and anhydrous ethanol and zirconia balls were added for ball milling. The mass ratio of zirconia balls, oxide powder and anhydrous ethanol was 2:1:0.6. The ball milling speed was 350 rpm. After 24 hours of ball milling, a uniformly mixed slurry A was obtained. S2: Put slurry A into a drying oven and dry it at 80°C for 18 hours to obtain a dry mixed powder, then grind the dry mixed powder with a mortar for 6 minutes, sieve the ground mixed powder with a 400-mesh sieve, and then introduce the sieved mixed powder into a cylindrical briquetting mold, and use a tablet press to press it. The tablet press pressure is 15MPa, and the prefabricated embryo body is obtained after maintaining the pressure for 10 minutes; S3: The prefabricated embryo body is placed in an alumina crucible and placed in a sintering furnace for firing at a temperature of 1300°C for 30 minutes, and then the fired embryo body is crushed into powder, and anhydrous ethanol and zirconium oxide balls are added to the powder, and the mass ratio of zirconium oxide balls, oxide powder and anhydrous ethanol is 2:1:0.6; the ball milling speed is 450rpm, and after ball milling for 36 hours, a uniformly mixed slurry B is obtained; S4: Put slurry B into a drying oven and dry it at 90°C for 30 hours to obtain a dry mixed powder, then grind it with a mortar, grind it for 6 minutes, sieve the ground mixed powder with a 500-mesh screen, add 8% polyvinyl alcohol by weight to the sieved mixed powder, grind it for 6 minutes to granulate, and then introduce the obtained granules into a cylindrical briquetting mold, and use a tablet press to press, firstly, press it at a pressure of 30MPa for 15 minutes to obtain a preformed embryo, and then press it at a pressure of 300MPa for 7 minutes to obtain an embryo body; S5: The embryo is placed in an alumina crucible and placed in a sintering furnace for firing. The sintering furnace is heated from room temperature to 1000°C at a heating rate of 10°C / min, and then heated to 1550°C at a heating rate of 5°C / min. After being kept at this temperature for 20 hours, the temperature is then raised to 1800°C at a heating rate of 5°C / min. The temperature is then stopped and cooled to room temperature to obtain (Hf 0.23 Zr 0.23 Ce 0.23 Pr 0.23 Y 0.08 ) 1.8 .
[0020] Example 2 A high entropy ceramic material, the chemical formula of which is (Hf 0.2 Zr 0.2 Ce 0.2 Pr 0.2 Y 0.2 ) 1.9 , and its preparation method comprises the following steps: S1: ZrO2 powder, HfO2 powder, CeO2 powder, Pr6O 11 The powder and Y2O3 powder were placed in a zirconia crucible respectively and calcined at 800°C for 3h to remove moisture and organic impurities in each oxide powder, so that the purity of each oxide powder was ≥99.9%. Then, the calcined ZrO2 powder, HfO2 powder, CeO2 powder, Pr6O 11 The powder and Y2O3 powder were placed in a zirconia ball mill, and anhydrous ethanol and zirconia balls were added for ball milling. The mass ratio of zirconia balls, oxide powder and anhydrous ethanol was 2:1:0.5. The ball milling speed was 300 rpm. After ball milling for 12 hours, a uniformly mixed slurry A was obtained. S2: Put slurry A into a drying oven and dry it at 70°C for 12 hours to obtain a dry mixed powder, then grind the dry mixed powder with a mortar for 5 minutes, sieve the ground mixed powder with a 300-mesh sieve, and then introduce the sieved mixed powder into a cylindrical briquetting mold, and use a tablet press to press it. The tablet press pressure is 10MPa, and the prefabricated embryo body is obtained after maintaining the pressure for 8 minutes; S3: The prefabricated embryo body is placed in an alumina crucible and placed in a sintering furnace for firing at a temperature of 1200°C for 50 minutes, and then the fired embryo body is crushed into powder, and anhydrous ethanol and zirconium oxide balls are added to the powder, and the mass ratio of zirconium oxide balls, oxide powder and anhydrous ethanol is 2:1:0.6; the ball milling speed is 400 rpm, and after ball milling for 50 hours, a uniformly mixed slurry B is obtained; S4: Put slurry B into a drying oven and dry it at 80°C for 40 hours to obtain a dry mixed powder, which is then ground with a mortar. After grinding for 7 minutes, the ground mixed powder is sieved with a 500-mesh sieve, and then 8% of the total weight of polyvinyl alcohol is added to the sieved mixed powder, and the powder is ground for 5 minutes. Then, the particles obtained after grinding are introduced into a cylindrical briquetting mold and pressed with a tablet press. First, the preformed green embryo is obtained by pressing at a pressure of 20 MPa for 10 minutes, and then the embryo body is obtained by pressing at a pressure of 250 MPa for 5 minutes. S5: The embryo is placed in an alumina crucible and placed in a sintering furnace for firing. The sintering furnace is heated from room temperature to 1000°C at a heating rate of 10°C / min, and then heated to 1550°C at a heating rate of 5°C / min. After being kept at this temperature for 20 hours, the temperature is then raised to 1800°C at a heating rate of 5°C / min. The temperature is then stopped and cooled to room temperature to obtain (Hf 0.2 Zr 0.2 Ce 0.2 Pr 0.2 Y 0.2 ) 1.9 .
[0021] Example 3 A high entropy ceramic material, the chemical formula of which is (Hf 0.15 Zr 0.15 Ce 0.15 Pr 0.15 Y 0.4 ) 1.6 , and its preparation method comprises the following steps: S1: ZrO2 powder, HfO2 powder, CeO2 powder, Pr6O 11The powder and Y2O3 powder were placed in zirconia crucibles respectively and calcined at 1000°C for 2h to remove moisture and organic impurities in each oxide powder, so that the purity of each oxide powder was ≥99.9%. Then, the calcined ZrO2 powder, HfO2 powder, CeO2 powder, Pr6O 11 The powder and Y2O3 powder were placed in a zirconia ball mill, and anhydrous ethanol and zirconia balls were added for ball milling. The mass ratio of zirconia balls, oxide powder and anhydrous ethanol was 2:1:0.6. The ball milling speed was 400 rpm. After 48 hours of ball milling, a uniformly mixed slurry A was obtained. S2: Put slurry A into a drying oven and dry it at 90°C for 24 hours to obtain a dry mixed powder, then grind the dry mixed powder with a mortar for 7 minutes, sieve the ground mixed powder with a 500-mesh sieve, and then introduce the sieved mixed powder into a cylindrical briquetting mold, and use a tablet press to press it. The tablet press pressure is 20MPa, and the prefabricated embryo body is obtained after maintaining the pressure for 10 minutes; S3: The prefabricated embryo body is placed in an alumina crucible and placed in a sintering furnace for firing at a temperature of 1400°C for 25 minutes, and then the fired embryo body is crushed into powder, and anhydrous ethanol and zirconium oxide balls are added to the powder, and the mass ratio of zirconium oxide balls, oxide powder and anhydrous ethanol is 2:1:0.5; the ball milling speed is 500 rpm, and after ball milling for 20 hours, a uniformly mixed slurry B is obtained; S4: Put slurry B into a drying oven and dry it at 100° C. for 20 hours to obtain a dry mixed powder, which is then ground with a mortar. After grinding for 5 minutes, the ground mixed powder is sieved with a 600-mesh screen, and then 8% of polyvinyl alcohol by weight is added to the sieved mixed powder. Grind for 7 minutes to granulate, and then introduce the obtained granules into a cylindrical briquetting mold and press them with a tablet press. First, the preformed green embryo is obtained by pressing at a pressure of 40 MPa for 20 minutes, and then the embryo body is obtained by pressing at a pressure of 300 MPa for 8 minutes. S5: The embryo is placed in an alumina crucible and placed in a sintering furnace for firing. The sintering furnace is heated from room temperature to 1000°C at a heating rate of 10°C / min, and then heated to 1550°C at a heating rate of 5°C / min. After being kept at this temperature for 20 hours, the temperature is then raised to 1800°C at a heating rate of 5°C / min. The temperature is then stopped and cooled to room temperature to obtain (Hf 0.15 Zr 0.15 Ce 0.15 Pr 0.15 Y 0.4 ) 1.6.
[0022] Comparative Example 1 A ceramic material with the chemical formula (ZrO2) 0.92 (Y2O3) 0.08 , and its preparation method comprises the following steps: S1: ZrO2 powder and Y2O3 powder were placed in zirconia crucibles respectively, and calcined at 900°C for 2.5h to remove moisture and organic impurities in each oxide powder; then, the calcined ZrO2 powder and Y2O3 powder were placed in a zirconia ball milling jar according to the mass ratio of ZrO2 to Y2O3 being 92:8, and anhydrous ethanol and zirconia balls were added for ball milling, and the mass ratio of zirconia balls, oxide powder and anhydrous ethanol was 2:1:0.6; the ball milling speed was 350rpm, and a uniformly mixed slurry A was obtained after ball milling for 24h; S2: Put slurry A into a drying oven and dry it at 80°C for 18 hours to obtain a dry mixed powder, then grind the dry mixed powder with a mortar for 6 minutes, sieve the ground mixed powder with a 400-mesh sieve, and then introduce the sieved mixed powder into a cylindrical briquetting mold, and use a tablet press to press it. The tablet press pressure is 15MPa, and the prefabricated embryo body is obtained after maintaining the pressure for 10 minutes; S3: The prefabricated embryo body is placed in an alumina crucible and placed in a sintering furnace for firing at a temperature of 1300°C for 30 minutes, and then the fired embryo body is crushed into powder, and anhydrous ethanol and zirconium oxide balls are added to the powder, and the mass ratio of zirconium oxide balls, oxide powder and anhydrous ethanol is 2:1:0.6; the ball milling speed is 450rpm, and after ball milling for 36 hours, a uniformly mixed slurry B is obtained; S4: Put slurry B into a drying oven and dry it at 90°C for 30 hours to obtain a dry mixed powder, then grind it with a mortar, grind it for 6 minutes, sieve the ground mixed powder with a 500-mesh screen, add 8% polyvinyl alcohol by weight to the sieved mixed powder, grind it for 6 minutes to granulate, and then introduce the obtained granules into a cylindrical briquetting mold, and use a tablet press to press, firstly, press it at a pressure of 30MPa for 15 minutes to obtain a preformed embryo, and then press it at a pressure of 300MPa for 7 minutes to obtain an embryo body; S5: The embryo is placed in an alumina crucible and placed in a sintering furnace for firing. The sintering furnace is heated from room temperature to 1000°C at a heating rate of 10°C / min, and then heated to 1550°C at a heating rate of 5°C / min. After being kept at this temperature for 20 hours, the temperature is then raised to 1800°C at a heating rate of 5°C / min. The temperature is then stopped and cooled to room temperature to obtain (ZrO2) 0.92 (Y2O3) 0.08.
[0023] Comparative Example 2 A ceramic material with the chemical formula (Hf 0.25 Zr 0.25 Ce 0.25 Y 0.25 )O2, and its preparation method comprises the following steps: S1: ZrO2 powder, HfO2 powder, CeO2 powder and Y2O3 powder with a particle size of 40-100 nm are placed in zirconia crucibles respectively, and calcined at 900°C for 2.5h to remove moisture and organic impurities in each oxide powder, so that the purity of each oxide powder is ≥99.9%; then, according to the molar ratio of Hf, Zr, Ce and Y being 0.25:0.25:0.25:0.25, the calcined ZrO2 powder, HfO2 powder, CeO2 powder and Y2O3 powder are placed in a zirconia ball mill, and anhydrous ethanol and zirconia balls are added for ball milling, and the mass ratio of zirconia balls, oxide powder and anhydrous ethanol is 2:1:0.6; the ball milling speed is 350rpm, and after ball milling for 24h, a uniformly mixed slurry A is obtained; S2: Put slurry A into a drying oven and dry it at 80°C for 18 hours to obtain a dry mixed powder, then grind the dry mixed powder with a mortar for 6 minutes, sieve the ground mixed powder with a 400-mesh sieve, and then introduce the sieved mixed powder into a cylindrical briquetting mold, and use a tablet press to press it. The tablet press pressure is 15MPa, and the prefabricated embryo body is obtained after maintaining the pressure for 10 minutes; S3: The prefabricated embryo body is placed in an alumina crucible and placed in a sintering furnace for firing at a temperature of 1300°C for 30 minutes, and then the fired embryo body is crushed into powder, and anhydrous ethanol and zirconium oxide balls are added to the powder, and the mass ratio of zirconium oxide balls, oxide powder and anhydrous ethanol is 2:1:0.6; the ball milling speed is 450rpm, and after ball milling for 36 hours, a uniformly mixed slurry B is obtained; S4: Put slurry B into a drying oven and dry it at 90°C for 30 hours to obtain a dry mixed powder, then grind it with a mortar, grind it for 6 minutes, sieve the ground mixed powder with a 500-mesh screen, add 8% polyvinyl alcohol by weight to the sieved mixed powder, grind it for 6 minutes to granulate, and then introduce the obtained granules into a cylindrical briquetting mold, and use a tablet press to press, firstly, press it at a pressure of 30MPa for 15 minutes to obtain a preformed embryo, and then press it at a pressure of 300MPa for 7 minutes to obtain an embryo body; S5: The embryo is placed in an alumina crucible and placed in a sintering furnace for firing. The sintering furnace is heated from room temperature to 1000°C at a heating rate of 10°C / min, and then heated to 1550°C at a heating rate of 5°C / min. After being kept at this temperature for 20 hours, the temperature is then raised to 1800°C at a heating rate of 5°C / min. The temperature is then stopped and cooled to room temperature to obtain (Hf 0.25 Zr 0.25 Ce 0.25 Y 0.25 )O2.
[0024] Comparative Example 3 A ceramic material with the chemical formula (Hf 0.2 Zr 0.2 Ce 0.2 Y 0.2 La 0.2 )O2, and its preparation method comprises the following steps: S1: ZrO2 powder, HfO2 powder, CeO2 powder, Y2O3 powder and La2O3 powder with a particle size of 40-100 nm are placed in zirconia crucibles respectively, and calcined at 900°C for 2.5h to remove moisture and organic impurities in each oxide powder, so that the purity of each oxide powder is ≥99.9%; then, according to the molar ratio of Hf, Zr, Ce, Y and La being 0.2:0.2:0.2:0.2:0.2, the calcined ZrO2 powder, HfO2 powder, CeO2 powder, Y2O3 powder and La2O3 powder are placed in a zirconia ball mill, and anhydrous ethanol and zirconia balls are added for ball milling, and the mass ratio of zirconia balls, oxide powder and anhydrous ethanol is 2:1:0.6; the ball milling speed is 350rpm, and after ball milling for 24h, a uniformly mixed slurry A is obtained; S2: Put slurry A into a drying oven and dry it at 80°C for 18 hours to obtain a dry mixed powder, then grind the dry mixed powder with a mortar for 6 minutes, sieve the ground mixed powder with a 400-mesh sieve, and then introduce the sieved mixed powder into a cylindrical briquetting mold, and use a tablet press to press it. The tablet press pressure is 15MPa, and the prefabricated embryo body is obtained after maintaining the pressure for 10 minutes; S3: The prefabricated embryo body is placed in an alumina crucible and placed in a sintering furnace for firing at a temperature of 1300°C for 30 minutes, and then the fired embryo body is crushed into powder, and anhydrous ethanol and zirconium oxide balls are added to the powder, and the mass ratio of zirconium oxide balls, oxide powder and anhydrous ethanol is 2:1:0.6; the ball milling speed is 450rpm, and after ball milling for 36 hours, a uniformly mixed slurry B is obtained; S4: Put slurry B into a drying oven and dry it at 90°C for 30 hours to obtain a dry mixed powder, then grind it with a mortar, grind it for 6 minutes, sieve the ground mixed powder with a 500-mesh screen, add 8% polyvinyl alcohol by weight to the sieved mixed powder, grind it for 6 minutes to granulate, and then introduce the obtained granules into a cylindrical briquetting mold, and use a tablet press to press, firstly, press it at a pressure of 30MPa for 15 minutes to obtain a preformed embryo, and then press it at a pressure of 300MPa for 7 minutes to obtain an embryo body; S5: The embryo is placed in an alumina crucible and placed in a sintering furnace for firing. The sintering furnace is heated from room temperature to 1000°C at a heating rate of 10°C / min, and then heated to 1550°C at a heating rate of 5°C / min. After being kept at this temperature for 20 hours, the temperature is then raised to 1800°C at a heating rate of 5°C / min. The temperature is then stopped and cooled to room temperature to obtain (Hf 0.2 Zr 0.2 Ce 0.2 Y 0.2 La 0.2 )O2.
[0025] Experimental example 1. Structural test X-ray diffraction tests were performed on the samples prepared in Examples 1 to 3 and Comparative Example 1. The results are as follows: Figure 1 As shown by Figure 1 It can be seen that the XRD results of the samples in the examples coincide with the diffraction peaks of the standard card (PDF#38-1439), indicating that the samples prepared by the solid phase synthesis method in the present application present a single-phase cubic fluorite structure.
[0026] The microscopic morphology of the samples prepared in Examples 1 to 3 and Comparative Example 1 was observed using a scanning electron microscope. Figures 2~5 As shown in the figure, it can be seen that the structure of the samples prepared in the embodiment is relatively dense, and there are still different degrees of porosity on the surface of ceramic blocks with different components.
[0027] The element distribution of the samples prepared in Examples 1 to 3 and Comparative Example 1 was analyzed using an energy spectrometer. The element distribution diagrams of the samples are shown in FIG. Figure 6 shown.
[0028] 2. Anti-CMAS performance test ① Preparation of CMAS powder According to the molar ratio of CaO, MgO, Al2O3 and SiO2 of 33:9:13:45, the oxide powders were weighed and placed in a mortar, and the oxide powders were fully ground until the oxides were evenly mixed; then the mixed oxide powders were placed in an alumina crucible, put into a high-temperature furnace and sintered at 1400°C for 2 hours, and then cooled with the furnace. The sintered powder was ground again and passed through a 500-mesh sieve. The sieved powder was CMAS powder.
[0029] ② The surfaces of the samples prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were ground and polished, and then the surfaces of the samples were cleaned with alcohol. Then, the prepared CMAS powder was heated to 15 mg / cm 3 The sample surface was evenly coated with a coating amount of 200 g / cm2 and then placed in an alumina crucible and placed in a sintering furnace for high-temperature reaction. The corrosion temperature was 1300°C and the corrosion time was set to 1h, 4h and 12h. After the corrosion was completed, the corrosion area of the sample was characterized by XRD, SEM and EDS, and then the corrosion depth of each sample was compared to determine the corrosion performance. The cross-sectional electron microscope scanning images of each sample after CMAS corrosion for 1h, 4h and 12h are shown in Figure 2. Figures 7-9 As shown, (a), (b), (c), and (d) are samples prepared in comparative example 1, example 1, example 2, and example 3, respectively. It can be seen from the figure that the corrosion reaction layer generated between the ceramic layer and the CMAS layer in the example sample is composed of two phases of long strips of apatite (Ca2RE8(SiO4)6O2) and a blocky cubic phase (c-ZrO2) stabilized by rare earth elements through EDS spectrum scanning; the CMAS element in the example sample only exists in the corrosion reaction layer and the CMAS residual layer, preventing CMAS from further penetrating into the ceramic layer. The statistics of the corrosion layer or corrosion reaction layer depth of the example and comparative example samples are shown in Table 1. Combined with the chart, it can be seen that the corrosion depth and corrosion rate of the example sample are lower than those of the comparative example. The example sample shows excellent anti-CMAS corrosion performance, and CMAS does not penetrate into the ceramic layer during the entire corrosion process.
[0030] Table 1
[0031] 3. Thermal conductivity test The thermal diffusion coefficient of the ceramic block was measured by the laser flash method. The instrument used was a laser thermal conductivity meter (LFA-427, Germany). The test temperature was set before the test. The laser source emitted a light pulse that evenly irradiated the lower surface of the sample. After the surface absorbed the light energy, its temperature instantly rose, and as the hot end, it transferred the energy to the upper surface in the form of heat conduction. During the transmission process, an infrared detector was used to continuously measure the temperature rise process at the center of the upper surface, and finally a curve of the relationship between the sample temperature and time was obtained. Then, the thermal diffusion coefficient was calculated using formula (1-1).α , in the formula, d and t 1 / 2 They represent the thickness of the sample and half of the time it takes for the upper surface to reach the highest temperature after absorbing heat. Then the thermal conductivity λ of the sample is calculated by formula (1-2). ρ and C Represent the density and specific heat capacity of the test sample respectively.
[0032] (1-1) (1-2) The unit of thermal conductivity is W·m -1 ·k -1 The results are shown in Table 2; it can be seen from the table that the thermal conductivity of the example samples is significantly lower than that of the comparative example samples.
[0033] Table 2
[0034] 4. Thermal expansion performance test The contact differential method was used to measure the thermal expansion coefficients of the examples and comparative examples at different temperatures. During the test, the thermal expansion coefficient error was almost negligible. The standard sample was placed in the thermal expansion instrument and the temperature was raised to measure the thermal expansion difference. Δl The temperature difference before and after heating Δt The thermal expansion difference in the test is due to the different degrees of thermal expansion behavior between the quartz glass rod and the test sample during the heating process. Then the thermal expansion coefficient of the sample is calculated using formula (1-3) α ,in, α s Indicates the thermal expansion coefficient of quartz glass material.
[0035] (1-3) The test results are shown in Table 3; it can be seen from the table that the thermal expansion coefficient of the example sample is significantly lower than that of the comparative example sample. When it is used to prepare thermal barrier coating materials, the prepared material can better withstand temperature fluctuations and maintain the stability of the material shape.
[0036] Table 3
[0037] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.
Claims
1. A high entropy ceramic material, characterized in that: The chemical formula of the high entropy ceramic material is (Hf (1-x) / 4 Zr (1-x) / 4Ce (1-x) / 4 Pr (1-x) / 4 Y x ) 2-δ , where the value range of X is 0.08~0.4, and the value range of δ is 0.1~0.
4.
2. The method for preparing the high entropy ceramic material according to claim 1, characterized in that: The following steps are involved: S1: The pretreated oxide powders are mixed according to the element composition in the chemical formula, and the mixture is mixed with a dispersant and ball-milled to obtain slurry A. The oxide powders include ZrO2 powder, HfO2 powder, CeO2 powder, Pr6O 11 powder and Y2O3 powder; S2: drying, grinding, sieving and pressing the slurry A to obtain a prefabricated embryo body; S3: firing the prefabricated body, then crushing the fired body into powder, mixing the powder with the dispersant and ball milling to obtain slurry B; S4: drying, grinding, sieving, granulating and pressing the slurry B to obtain an embryo body; S5: sintering the embryo to obtain.
3. The method for preparing a high entropy ceramic material according to claim 2, characterized in that: The pretreatment of the oxide powder in step S1 is as follows: calcining at 800-1000°C for 2-3h; the particle size of the oxide powder is 40-100nm; ZrO2 powder, HfO2 powder, CeO2 powder, Pr6O 11 The purity of powder and Y2O3 powder is ≥99.9%.
4. The method for preparing a high entropy ceramic material according to claim 3, characterized in that: The dispersant is anhydrous ethanol, and the mass ratio of the oxide powder to the anhydrous ethanol in step S1 is 1:0.5-0.6; the ball milling speed in step S1 is 300-400 rpm, and the ball milling time is 12-48 hours.
5. The method for preparing a high entropy ceramic material according to claim 4, characterized in that: In step S2, the drying temperature is 70-90° C., the drying time is 12-24 h, the grinding time is 5-7 min, the sieving mesh number is 300-500 mesh, and the tablet press is used for pressing, the pressure is 10-20 MPa, and the pressing time is 8-10 min.
6. The method for preparing a high entropy ceramic material according to claim 5, characterized in that: In step S3, the firing temperature is 1200-1400° C., the firing time is 25-50 min, the mass ratio of powder to anhydrous ethanol is 1:0.5-0.6, the ball milling speed is 400-500 rpm, and the ball milling time is 20-50 h.
7. The method for preparing a high entropy ceramic material according to claim 6, characterized in that: In step S4, the drying temperature is 80-100° C., the drying time is 20-40 hours, the grinding time is 5-7 minutes, the sieving mesh number is 500-600 mesh, and the granulation operation is: add 8% of the total weight of polyvinyl alcohol to the sieved mixed powder and grind for 5-7 minutes.
8. The method for preparing a high entropy ceramic material according to claim 7, characterized in that: The pressing operation in step S4 is: using a tablet press to maintain pressure and press for 10 to 20 minutes at a pressure of 20 to 40 MPa, and then to maintain pressure and press for 5 to 8 minutes at a pressure of 250 to 300 MPa.
9. The method for preparing a high entropy ceramic material according to claim 8, characterized in that: The firing method in step S5 is: heating to 1000°C at a heating rate of 10°C / min, then heating to 1550°C at a heating rate of 5°C / min, keeping the temperature for 20 hours, then heating to 1800°C at a heating rate of 5°C / min, then stopping heating and cooling to room temperature.
10. An application of a high entropy ceramic material, characterized in that: The high entropy ceramic material according to claim 1 is used to prepare a thermal barrier coating material.
Citation Information
Patent Citations
Complex oxide thermal barrier coatings with low thermal inertia and low thermal conductivity
CA3197162A1
High-entropy composite oxide and preparation method and application thereof
CN118458819A
Preparation method of DLP photocuring 3D printing high-entropy fluorite oxide ceramic
CN118978406A
Fluorite-pyrochlore double-phase high-entropy oxide ceramic powder and preparation method thereof
CN119100790A
Thermal Barrier Coating for CMAS Resistance and Low Thermal Conductivity
US20150336850A1